Black Lives Matter and the impact on human resources - Alotaibi, Nada (Eximia, 2022)
The occurrence of the Black Live Matter protests has led to media focus on racial inequality in organizations. Expectations are that the management of the various organizations realize that they have a social responsibility to their customers and other stakeholders to ensure that their workplaces are inclusive and diversified. Many organizations were forced to react to Black Lives Matters’ protests of 2020 as a way of showing solidarity with the Black community in its demand for equal treatment of its members. However, Black Lives Matter protests and appeals are less likely to affect the managerial process of the HR managers of most large organizations significantly. Aspects such as human resource planning, employee remuneration, and benefits administrations, performance management, and employee relations are less likely to witness any change. Such events have occurred in the past, but little transformations have been made in the managerial process of these organizations.